A Perspective on Balance and the Role of Law - Palmer, Matthew SR (Victoria University of Wellington Law Review, 2023)
This article provides an overview of the "Roles and Perspectives in the Law" conference held in honour of the Rt Hon Sir Ivor Richardson and discusses the themes running through various areas of law by exploring the notion of balance. The varied perspectives in the conference papers demonstrate that, where interests are in opposition to each other, the law that regulates strikes a balance between them at some point. Palmer explores this idea through well-established "black-letter" law (such as employment, taxation, and commercial law) and the less established "red-letter" law (such as human rights, indigenous peoples’ rights, and constitutional design). It is argued that judges have a crucial role to play in striking a balance in both categories of law. The author concludes that, whether it is black- or red-letter law, it is human behaviour that is being regulated; therefore, one must be careful not to divide human behaviour into neat categorical boxes.